2017
DOI: 10.1002/anie.201702099
|View full text |Cite
|
Sign up to set email alerts
|

Lithiophilic Sites in Doped Graphene Guide Uniform Lithium Nucleation for Dendrite‐Free Lithium Metal Anodes

Abstract: Lithium (Li) metal is the most promising electrode for next-generation rechargeable batteries. However, the challenges induced by Li dendrites on a working Li metal anode hinder the practical applications of Li metal batteries. Herein, nitrogen (N) doped graphene was adopted as the Li plating matrix to regulate Li metal nucleation and suppress dendrite growth. The N-containing functional groups, such as pyridinic and pyrrolic nitrogen in the N-doped graphene, are lithiophilic, which guide the metallic Li nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
801
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,059 publications
(827 citation statements)
references
References 42 publications
18
801
4
4
Order By: Relevance
“…2 mm) are grown vertically on the electrode when using normal electrolyte (Figure 5d), which is larger than those cycled at 1mAcm À2 and more likely to cause short circuit. [30] Therefore,t here is an egative correlation between zinc dendrite sizes and current densities.At the low current density,z inc tends to be grown largely and dispersedly owing to the less activate sites on the surface which can achieve sufficient energy for zinc nucleation. Figure 5g clearly demonstrates the change trends of cycle life with current densities.I tis obvious that PA Ma dditive can significantly promote the cycle stability in aw ide range of current densities.F urthermore,t he average voltage hysteresis at different current densities and its difference between the two kinds of the electrolyte is summarized in the Supporting Information, Table S1.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…2 mm) are grown vertically on the electrode when using normal electrolyte (Figure 5d), which is larger than those cycled at 1mAcm À2 and more likely to cause short circuit. [30] Therefore,t here is an egative correlation between zinc dendrite sizes and current densities.At the low current density,z inc tends to be grown largely and dispersedly owing to the less activate sites on the surface which can achieve sufficient energy for zinc nucleation. Figure 5g clearly demonstrates the change trends of cycle life with current densities.I tis obvious that PA Ma dditive can significantly promote the cycle stability in aw ide range of current densities.F urthermore,t he average voltage hysteresis at different current densities and its difference between the two kinds of the electrolyte is summarized in the Supporting Information, Table S1.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Coinciding well with Cui's results, there is no nucleation overpotential for Li deposition on the Ag/CNF substrate and Li prominently nucleates and grows on the Ag nanoseeds, resulting in a uniform Li film along the CNFs during Li platting. Afterward, the materials options were further broadened by Zhang et al In addition to metals, they found that different Li nucleation behavior can also be observed from other non-metallic materials such as carbon [343]. The results showed that negligible nucleation overpotential for Li deposition was observed on nitrogen-doped graphene (NG), while obvious nucleation overpotential was observed for its counterparts (graphene and Cu foil).…”
Section: Selective Depositionmentioning
confidence: 99%
“…[21] Thep orous and freestanding O f -CNT with specific surface area of 174.9 m 2 g À1 was latter used as a3 Dc onducting scaffold to accommodate Na metal without additional current collectors (Supporting Information, Figures S1-S3). [22,23] TheO1s spectra of asprepared O f -CNT (Supporting Information, Figure S7) exhibited three peaks assigned to ether oxygen (534.8 eV), carbonyl oxygen (533.2 eV), and oxhydryl oxygen (531.2 eV). A2 4.4 atom %Ocontent was generally utilized for O f -CNT in this work if not otherwise specified (Supporting Information, Figures S5 and S6).…”
Section: Angewandte Chemiementioning
confidence: 99%